Challenges of Sustainable Urban Development in the Context of Population Growth - Profiroiu, Constantin Marius; Bodislav, Dumitru Alexandru; Burlacu, Sorin; Rădulescu, Carmen Valentina (European Journal of Sustainable Development, 2020)
Lately, we face many challenges that threaten the well-being of society and the quality of life. All of these challenges are complex and closely related, which means that one approach can have positive consequences for others. In this context, population growth, an extremely delicate subject, from a social and ethical point of view has generally become a threat to the entire planet, and in particular, to urban agglomerations. At the global level, population growth puts even greater pressure on basic resources, from fresh water to fertile land, endangering the very existence of humanity. The purpose of this paper is to analyze the population trend globally, as compared to the population trend in the big urban agglomerations, as well as the evolution of some indicators of the quality of life depending on the population growth. Following the analysis, we aim to identify various challenges and develop proposals for the sustainable development of urban space.